2021
DOI: 10.1002/prca.202100002
|View full text |Cite
|
Sign up to set email alerts
|

Plasma proteomics analysis of adolescent idiopathic scoliosis patients revealed by Quadrupole‐Orbitrap mass spectrometry

Abstract: We aim to investigate the changes of plasma proteome among mild, severe adolescent idiopathic scoliosis (AIS) patients and healthy controls. Methods: In this retrospective study, there were 84 individuals including 56 confirmed AIS patients (27 follow-up AIS patients and 29 surgical AIS patients) and another 28 healthy teenagers. Plasma samples were obtained and Quadrupole-Orbitrap Mass Spectrometer was performed to identify proteins in AIS patients and control group. T-test and ANOVA were performed to screen … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 45 publications
0
4
0
Order By: Relevance
“…105 Initial studies found increased levels of calmodulin in platelets of patients with AIS, and the level appeared related to the curve progression of AIS. [105][106][107] While the involvement of platelet calmodulin in AIS was unclear, it was proposed as a possible marker for AIS. Later studies have focused on the correlation between platelet calmodulin level and the progression of AIS, and the correlation between calmodulin gene polymorphism and AIS.…”
Section: Calmodulin In Aismentioning
confidence: 99%
See 1 more Smart Citation
“…105 Initial studies found increased levels of calmodulin in platelets of patients with AIS, and the level appeared related to the curve progression of AIS. [105][106][107] While the involvement of platelet calmodulin in AIS was unclear, it was proposed as a possible marker for AIS. Later studies have focused on the correlation between platelet calmodulin level and the progression of AIS, and the correlation between calmodulin gene polymorphism and AIS.…”
Section: Calmodulin In Aismentioning
confidence: 99%
“…Initial studies found increased levels of calmodulin in platelets of patients with AIS, and the level appeared related to the curve progression of AIS 105‐107 . While the involvement of platelet calmodulin in AIS was unclear, it was proposed as a possible marker for AIS.…”
Section: Calmodulin In Aismentioning
confidence: 99%
“…The filtrate was discarded after centrifugation at 14,000g for 10 minutes. Subsequently, the samples were treated with dithiothreitol (Sigma, USA) and iodoacetamide (Sigma, USA), followed by digestion into peptides using trypsin (Promega, USA) according to the previously published methods ( 13 ). Finally, the desiccated peptides were resuspended in 0.1% formic acid for LC-MS/MS proteome analysis.…”
Section: Methodsmentioning
confidence: 99%
“…For example, it has been found that the levels of plasma oxoglutarate, arginine, N-acetylaspartate, and citrate were significantly increased, whereas the levels of fumarate, glutamate, L-glutamic acid, malate, and N-acetylglutamate were reduced in AIS patients [11]. Furthermore, proteome analysis has indicated that some proteins are under or overexpressed in AIS patients [12,13], e.g., fibronectin, calmodulin, and fibrinogen concentrations were significantly higher and positively correlated with the Cobb angle [14]. Disturbance in the lipid profile has also been suggested as a marker of AIS [15].…”
Section: Introductionmentioning
confidence: 99%